Reading in the Scenery of the performance and its developments (Al-Academy, 2024)
The importance of this research in studying the actor life existence on the stage through the performance art;where as all the literary theatrical dimensions didn't ignore the importance of the actor's performance. So, it is shed a light on the nature of the scenery in the actor's performance and what its representations in the temporary directions …….. The research set off from the imitation as a human instinct to the performance of the actor in post-modernity theater; so the researcher found that there is a question must be answered which is :Is the actor live a regression state in his theatrical performance ,or that the performance of the actor connect with collective conscience of human being which is repeated in certain conditions for the actor? Here, the researcher answers on these questions through presenting the performance scenery through the most important theatrical dimensions.